On‐Surface Synthesis and Collective Spin Excitations of a Triangulene‐Based Nanostar. Issue 48 (13th October 2021) - Hieulle, Jeremy; Castro, Silvia; Friedrich, Niklas; Vegliante, Alessio; Lara, Francisco Romero; Sanz, Sofía; Rey, Dulce; Corso, Martina; Frederiksen, Thomas; Pascual, Jose Ignacio; Peña, Diego
Abstract: Triangulene nanographenes are open‐shell molecules with predicted high spin state due to the frustration of their conjugated network. Their long‐sought synthesis became recently possible over a metal surface. Here, we present a macrocycle formed by six [3]triangulenes, which was obtained by combining the solution synthesis of a dimethylphenyl‐anthracene cyclic hexamer and the on‐surface cyclodehydrogenation of this precursor over a gold substrate. The resulting triangulene nanostar exhibits a collective spin state generated by the interaction of its 12 unpaired π‐electrons along the conjugated lattice, corresponding to the antiferromagnetic ordering of six S =1 sites (one per triangulene unit). Inelastic electron tunneling spectroscopy resolved three spin excitations connecting the singlet ground state with triplet states. The nanostar behaves close to predictions from the Heisenberg model of an S =1 spin ring, representing a unique system to test collective spin modes in cyclic systems. Abstract : A star‐shaped triangulene cyclic hexamer, which accumulates 12 unpaired electrons, was prepared by combining solution chemistry and on‐surface synthesis. The resulting triangulene‐based nanostar was visualized by bond‐resolved scanning tunneling microscopy on a gold substrate. The collective spin excitations, explained by the Heisenberg model, were revealed by inelastic electron tunneling spectroscopy.